ЕFFICIENCY OF STABILIZING MEDIA FOR LYOFILIZATION AND STORAGE ASSOCIATED VACCINE AGAINST PESTE DES PETITS RUMINANTS AND SHEEP POX (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Six stabilizing media consisting of peptone, lactose, sucrose, lactalbumin hydrolyzate,and gelatin were tested for their effectiveness in stabilizing the associated vaccine against peste despetits ruminants and sheep pox at lyophilization and storage. The effectiveness of the associatedvaccines containing various stabilizing composition was evaluated by the level of the biologicalactivity of the viruses, after their lyophilization and storage in different temperature-time regimes(minus 20°C, 4°C, (20–22)°C and (35–37)°C for 12 months., 7 days and 5 days, respectively)using specific sera. The control was the vaccine, dried without a protective environment. As aresult of the research, it was established that a complex medium consisting of peptone-lactose ata final concentration of 3% and 2%, respectively, are effective stabilizers in the lyophilization andstorage of the associated vaccine against peste des petits ruminants and sheep pox.
Keywords: associated vaccine, sheep pox, peste des petits ruminants, lyophilization, stabilizing media.